Legal histories of empire
1 online resource
Keywords: "This collection brings together an international group of scholars in order to provide new insights into the diversity of imperial legalities. Across empires, legalities were produced not just - or even - through the imperial imposition of laws and legal forms, but through local processes of negotiation and contestation. Far from the metropoles, local actors found ways to creatively navigate and subvert imperial frameworks and laws, and to create space in which to shape new legalities, responsive to local circumstance and need. Covering topics as diverse as smuggling in eighteenth century Jersey, the criminalisation of female market women in World War II-era southern Nigeria, and whiteness and race in 'sexual perversion' cases in twentieth century Malaya, the collection elaborates new legal histories of empire. Drawing from Britain, Australia, Canada, the USA, India, Sri Lanka, Africa and Malaysia, the collection brings together essays that examine the stories of the peoples of empires and shows how they constituted, experienced, navigated and subverted the legal complexities of living under empire. This book will be of interest to scholars and researchers in law and history, but also to those with relevant interests in post-colonial and cultural studies, as well as in criminology and sociology"--